2016
DOI: 10.2340/00015555-2279
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil, Sunflower Oil or no Oil for Baby Dry Skin or Massage: A Pilot, Assessor-blinded, Randomized Controlled Trial (the Oil in Baby SkincaRE [OBSeRvE] Study)

Abstract: Topical oils on baby skin may contribute to development of childhood atopic eczema. A pilot, assessor-blinded, randomized controlled trial assessed feasibility of a definitive trial investigating their impact in neonates. One-hundred and fifteen healthy, full-term neonates were randomly assigned to olive oil, sunflower oil or no oil, twice daily for 4 weeks, stratified by family history of atopic eczema. We measured spectral profile of lipid lamellae, trans-epidermal water loss (TEWL), stratum corneum hydratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 45 publications
2
78
1
8
Order By: Relevance
“…These activities are associated with the presence of fatty acids, including omega‐3 (α‐linolenic acid, 0.5%‐0.9%), omega‐6 (linoleic acid, 2%‐10%), and nonessential omega‐9 (oleic acid, up to 78%‐80%) fatty acids, squalene and phenolics . However, olive oil has been reported to disrupt the skin barrier, thereby acting as an irritant and causing erythema . Because a high amount of oleic acid is present in olive oil, such disruption is possibly a result of the interaction between SC lipids and oleic acid …”
Section: Introductionmentioning
confidence: 99%
“…These activities are associated with the presence of fatty acids, including omega‐3 (α‐linolenic acid, 0.5%‐0.9%), omega‐6 (linoleic acid, 2%‐10%), and nonessential omega‐9 (oleic acid, up to 78%‐80%) fatty acids, squalene and phenolics . However, olive oil has been reported to disrupt the skin barrier, thereby acting as an irritant and causing erythema . Because a high amount of oleic acid is present in olive oil, such disruption is possibly a result of the interaction between SC lipids and oleic acid …”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid fluidizes the barrier by displacing a number of the saturated acids . Additionally, many studies have demonstrated the positive effects of olive oil on wound recovery, as well as anti‐inflammatory and anti‐oxidative effects .…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study, Cooke and colleagues randomized 115 neonates to three treatment groups—no oil, four drops of olive oil, four drops of SSO—applied twice daily to the left side of the body for 4 weeks (Table ). No differences were observed in TEWL between the olive oil and no‐oil groups, but the olive oil–treated group had a significantly lower ordering of lipids in the stratum corneum than the no‐oil group as measured using ATR‐FTIR . A lower ordering of lipids suggests abnormal lamellar lipid development and is associated with poorer skin barrier function .…”
Section: Olive Oilmentioning
confidence: 91%
“…The use of olive oil for skin care dates back to ancient Egypt . Olive oil can be defined according to its ratio of fatty acids (palmitic acid, oleic acid, linoleic acid, linolenic acid), with oleic acid being the predominant component . Although the use of olive oil is popular in the United Kingdom, only a small number of studies have investigated its efficacy as an emollient.…”
Section: Olive Oilmentioning
confidence: 99%